Estratégias operacionais em biorreatores para pós-tratamento de efluente anaeróbio: ênfase na remoção de metano, sulfeto e nitrogênio amoniacal - Cássia Cabral e Souza (2020)
Anaerobic sewage treatment systems, such as UASB reactors, are one of the most used technologies in warm countries such as Brazil. Despite having lots of advantages, these reactors have some limitations such as methane (CH4) and sulfide (H2S) dissolved in the effluent and no nitrogen ammoniacal (NH3) removal. In this context, the effluents from anaerobic reactors usually require a post-treatment step to meet the discharge limits of environmental legislation and protect the water bodies. This study aims to evaluate the performance of two bioreactors: R-control and R-air in stage 1 and R-control and R-inoculum in stage 2 to post treat UASB effluent, treating domestic wastewater. The experiment was divided into two stages. In stage 1 was evaluated the effects of microaeration and sunlight in two phases (HRT 6h phase 1 and HRT 3h phase 2). In the stage 2 different intermittent aeration strategies (2min on/14min off, 7min on/14min off e 21min on/14min off), absence of light and inoculation were evaluated. In stage 1 large H2S and CH4 removal efficiencies were achieved by the microaerated reactor at HRT of 6 h. At this HRT, H2S removal efficiencies were equal to 61% and 79%, and CH4 removal efficiencies were 31% and 55% for R-control and R-air, respectively. At an HRT of 3 h, H2S removal efficiencies were 22% (R-control) and 33% (R-air) and CH4 removal did not occur. The complete oxidation of sulfide, with sulfate formation, prevailed in both phases and bioreactors. However, elemental sulfur formation was more predominant at an HRT of 6 h than at an HRT of 3 h.The results pointed that sunlight and microaeration favored biological methane and sulfur removal. Microbial community analysis confirmed by next generation sequencing (NGS) that the bacteria involved in the biological removal of methane (methanotrophic bacteria) and sulfide (sulfur and non sulfur bacteria) were present in the bioreactors. Nitrification did not occur in the bioreactors in both phases due absence of microorganisms in the nitrogen cycle. In the stage 2 the different intermittent aeration strategies and low dissolved oxygen concentrations did not contribute to nitrification in both bioreactors. Sulfide removal efficiencies were 42% in R-control and 36% in R-inoculum.